PEMANFAATAN EKSTRAK SEREH (CHYMBOPOGON NARDUS L.)SEBAGAI ALTERNATIF ANTI BAKTERI STAPHYLOCOCCUSEPIDERMIDIS PADA DEODORAN PARFUME SPRAY - Nenny Widiani, Retno Atun Khasanah, Eko Budiyanto , (Pelita - Jurnal Penelitian Mahasiswa UNY, 2011)
This experimental research was aimed at determining the effectiveness of using parfume spray deodorant with lemon grass extract on Staphylococcus epidermidis bacterial activity and to find out the optimum concentration oflemongrass extract in parfume spray deodorant to reduce Staphylococcus epidermidis activity.The research method included four steps, namely preparing lemongrass (Cymbopogon nardus L.) extract,making perfume spray deodorant, conducting laboratory test, and testing within a limited audience. Thisexperiment revealed that lemongrass (Cymbopogon nardus L.) extract could potentially be used as an anti‐bacteriaStaphylococcus epidermidis. Making perfume spray deodorant from lemongrass (Cymbopogon nardus L.) extractconsisted of two steps, preparing lemongrass (Cymbopogon nardus L.) extracts and mixing the lemongrass(Cymbopogon nardus L.) extract with alcohol and propylene glycol.Inhibition test of lemongrass (Cymbopogon nardus L.) extract on the growth of Staphylococcus epidermidisused Mueller‐Hinton media order. From the test results of each lemongrass (Cymbopogon nardus L.) extract in theconcentration of 5%, 15%, and 30%, inhibition results were obtained. They were 0 mm, 0 mm, and 14 mm, whilethe inhibition of standard perfume spray deodorant in the market was 8 mm . Based on the results, it can beconcluded that the inhibition of lemongrass (Cymbopogon nardus L.) extract on the growth of Staphylococcusepidermidis was effective and optimum at the concentration of 30%.Keywords: lemongrass extract, Staphylococcus epidermidis, perfume spray deodorant